Peramalan dan Analisis Subsektoral Nilai Tukar Petani (NTP) di Provinsi Jawa Timur - Rif'an Hariri (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The agricultural sector's contribution to the economy and food security in East Java province is so significant that it is necessary to consider the welfare of farmers. The farmer exchange rate, popularly called NTP, is a crucial indicator of farmer welfare. The first objective is to forecast the combined farmer exchange rate and subsector farmer exchange rate in East Java Province, and the second objective is to analyze the relationship between the subsector farmer exchange rate and the combined farmer exchange rate in East Java Province. Using multiple linear regression, the forecasting method used is triple exponential smoothing to analyze the relationship between the subsector farmer exchange rate and the combined farmer exchange rate. The results show that the combined farmer exchange rate in 2025 is predicted to decrease. The exchange rate of the subsector farmers is expected to decline in 2025, but only for food crops. The exchange rate of subsector farmers in food crops, horticulture, smallholder plantations, livestock, and fisheries simultaneously has a significant effect. It also has a considerable impact on the combined farmer exchange rate.